A CONTRASTIVE ANALYSIS OF EQUINE IDIOMS IN ENGLISH, SPANISH AND LITHUANIAN - Korostenskienė, Julija; Tarnauskaitė, Greta (Verbum, 2015)
Based on the assumption that language reflects the cultural constructs of its users, the article examines idioms containing equine component, i.e. those referring to horse and to donkey, in English, Spanish and Lithuanian. The data are collected from major phraseological dictionaries and are examined applying componential analysis, initially identifying basic meaning components characteristic of horse/donkey, dividing all idioms according to the positive or negative connotation contributed, and then establishing the idiom-distinctive meaning component. The analysis of idioms reveals that, apart from common areas of perceiving animals as a means of transportation, several language-specific traits can be identified, e.g. horse as used for racing specifically in British culture, or predominantly positive attitude to donkey (vs horse) in Spanish. The negative connotation is characteristic of all donkey idioms in Lithuanian. The results demonstrate that the negative connotation across the three languages is conveyed when the animal is attributed personifying features referring to human behaviour.
Keywords: phraseology; idioms; equine; componential analysis; English; Spanish; Lithuanian